Advances and Promises of 2D MXenes as Cocatalysts for Artificial Photosynthesis. Issue 12 (22nd October 2021) - Ding, Mingye; Han, Chenhui; Yuan, Yongjun; Xu, Jingsan; Yang, Xiaofei
Abstract : 2D MXenes have received growing attention as highly active and earth‐abundant cocatalysts for photocatalytic applications, due to their merits including rich surface chemistry, excellent electrical conductivity, distinct carrier mobility, and good hydrophilicity. In this review, the research progress on MXenes and MXene‐based composites in photocatalysis are systematically summarized and discussed. Based on the theoretical and experimental studies, this review focuses mainly on the synthetic methods of MXenes, the roles of MXenes in photocatalysis, the design strategies for MXene‐based composites and the state‐of‐the‐art applications of these MXene‐based materials in photocatalytic reactions, including water splitting, CO2 reduction, and nitrogen fixation. In addition, this review outlines the surface modification and enhancement mechanism from a material design and synthesis perspective, and highlights the pivotal challenges and potential opportunities in the field of MXene‐involved photocatalysis. Therefore, this review is expected to provide a useful reference for the development of MXene‐related photocatalytic applications. Abstract : The past decade has witnessed the rapid growth of 2D carbides and nitrides (2D MXenes), it has shown useful and tunable electronic, and optical properties for photocatalytic applications. Herein, the main strategies used for the construction of emerging 2D MXene‐based nanostructures for artificial photosynthesis are highlighted. The key challenges are discussed and future directions of this hot topic are outlined.